2005
DOI: 10.1002/jemt.20248
|View full text |Cite
|
Sign up to set email alerts
|

New application of air-drying techniques for studying Ephemeroptera and Plecoptera eggs by scanning electron microscopy

Abstract: Hexamethyldisilizane (HMDS) and tetramethylsilane are organic compounds that are volatile at ambient temperature and which can therefore be used for air-drying biological samples for SEM studies. The techniques using these compounds provide results that are comparable with those obtained by critical point drying, but which involve a very simple process that saves time and money. Both techniques were applied to SEM studies of Ephemeroptera and Plecoptera eggs in order to assess their suitability as alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…The use of HMDS is also a safer and cost-effective alternative to CPD. Several previous studies have shown that the use of HMDS yields comparable results as those obtained with identical biological specimens or sample tissues prepared with CPD (Bray et al, 1993, Hochberg and Litvaitis, 2000, Kennedy et al, 1989, Nation, 1983, Slizova et al, 2003, Ubero-Pascal et al, 2005. The data presented here demonstrate that application of HMDS to LVSEM sample preparation is appropriate for preserving and drying mammalian eggs and early zygotes.…”
supporting
confidence: 73%
“…The use of HMDS is also a safer and cost-effective alternative to CPD. Several previous studies have shown that the use of HMDS yields comparable results as those obtained with identical biological specimens or sample tissues prepared with CPD (Bray et al, 1993, Hochberg and Litvaitis, 2000, Kennedy et al, 1989, Nation, 1983, Slizova et al, 2003, Ubero-Pascal et al, 2005. The data presented here demonstrate that application of HMDS to LVSEM sample preparation is appropriate for preserving and drying mammalian eggs and early zygotes.…”
supporting
confidence: 73%
“…They were selected, rinsed, euthanised in water near to boil (except pupae), and fixed in McDowell fixative solution (4% formalin, 1% glutaraldehyde mixture in cacodylate buffer solution, pH 7.4) [46], at 4 8C for 24 h. Specimens were rinsed again twice in sodium cacodylate + sucrose solution 0.1 M, dehydrated until absolute acetone in a gradient of increasing concentration of ethanol and ethanol-acetone solution (50% of each reagent) and dried using critical point method or by air-drying after hexamethyldisilizane treatment [47]. Dried specimens were mounted on SEM stubs with conductive adhesive tape, mounting them in different positions (dorsal, lateral and ventral views).…”
Section: Methodsmentioning
confidence: 99%
“…In order to reduce costs and provide a similar effect to that proposed in Fang et al (2002), tetramethylsilane (TMS) will be used as a strong dehydrating agent that maintains tissue structure (Ubero-Pascal et al, 2005). Moreover, a series of investigations is set up to determine the specific way in which formalin acts to prevent amplification.…”
Section: Introductionmentioning
confidence: 99%